Skill Mismatches in the EU: Immigrants vs. Natives - Sandra Nieto; Alessia Matano; Raul Ramos (Institute for the Study of Labor (IZA), 2013)
The objective of this paper is to analyse and explain the factors behind the observed differences in skill mismatches (vertical and horizontal) between natives and immigrants in EU countries. Using microdata from the 2007 wave of the Adult Education Survey (AES), different probit models are specified and estimated to analyse differences in the probability of each type of skill mismatch between natives and immigrants. Next, Yun's decomposition method is used to identify the relative contribution of characteristics and returns to explain the differences between the two groups. Our analysis shows that immigrants are more likely to be skill mismatched than natives, being this difference much larger for vertical mismatch. In this case, the difference is higher for immigrants coming from non-EU countries than for those coming from other EU countries. We find that immigrants from non-EU countries are less valued in the EU labour markets than natives with similar characteristics, a result that is not observed for immigrants from EU countries. These results could be related to the limited transferability of the human capital acquired in non-EU countries. The findings suggest that specific programs to adapt immigrants' human capital acquired in home country are required to reduce differences in the incidence of skill mismatch and a better integration in the EU labour markets.
Keywords: J15; J24; J31; 330; immigrant overeducation; vertical mismatch; horizontal mismatch; human capital transferability